Geological relationships and laser ablation ICP-MS U-Pb geochronology of the Saint George Batholith, southwestern New Brunswick, Canada: implications for its tectonomagmatic evolution - Mohammadi, Nadia; Fyffe, Les; McFarlane, Christopher; Thorne, Kay; Lentz, David; Charnley, Brittany; Branscombe, Laurin; Butler, Sheena (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2017)
ABSTRACT The Late Silurian to Late Devonian Saint George Batholith in southwestern New Brunswick is a large composite intrusion (2000 km2) emplaced into the continental margin of the peri-Gondwanan microcontinent of Ganderia. The batholith includes: (1) Bocabec Gabbro; (2) equigranular Utopia and Wellington Lake biotite granites; (3) Welsford, Jake Lee Mountain, and Parks Brook peralkaline granites; (4) two-mica John Lee Brook Granite; (6) Jimmy Hill and Magaguadavic megacrystic granites; and (6) rapakivi Mount Douglas Granite. New LA ICP-MS in situ analyses of six samples from the Saint George Batholith are as follows: (1) U-Pb monazite crystallization age of 425.5 ± 2.1 Ma for the Utopia Granite in the western part of the batholith (2) U-Pb zircon crystallization ages of 420.4 ± 2.4 Ma and 420.0 ± 3.5 Ma for two samples of the Utopia Granite from the central part of the batholith; (3) U-Pb zircon crystallization age of 418.0 ± 2.3 Ma for the Jake Lee Mountain Granite; (4) U-Pb zircon crystallization age of 415.5 ± 2.1 Ma for the Wellington Lake Granite; and (5) U-Pb monazite crystallization age of 413.3 ± 2.1 Ma for the John Lee Brook Granite. The new geochronological together with new and existing geochemical data suggest that the protracted magmatic evolution of the Late Silurian to Early Devonian plutonic rocks is related to the transition of the Silurian Kingston arc-Mascarene backarc system from an extensional to compressional tectonic environment during collision of the Avalonian microcontinent with Laurentia followed by slab break-off.